2017
DOI: 10.1016/j.eats.2017.06.056
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic Intra-articular Spinoglenoid Cyst Resection Following SLAP Repair

Abstract: Spinoglenoid cyst (SGC) is a ganglion arising in the spinoglenoid notch and is thought to be related to SLAP lesion. This cyst often compresses the suprascapular nerve in the spinoglenoid notch. Symptomatic cysts require surgical treatment when conservative treatment fails. In particular, arthroscopic decompression through the torn labral tissue when the cyst is extending into the joint cavity is easy and convenient. However, if the cyst is confined to the spinoglenoid notch, arthroscopic approach through the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Some authors have reported a transcapsular technique of resecting the cyst in its entirety, with debridement of all margins of the cyst. This technique may be time-consuming and may still pose a risk to the SSN 16 . Our limited capsulectomy allows excellent visualization of the extent of the cyst, minimizes the chance of recurrence, is technically fast and simple to perform, and has shown good results with excellent reproducibility.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have reported a transcapsular technique of resecting the cyst in its entirety, with debridement of all margins of the cyst. This technique may be time-consuming and may still pose a risk to the SSN 16 . Our limited capsulectomy allows excellent visualization of the extent of the cyst, minimizes the chance of recurrence, is technically fast and simple to perform, and has shown good results with excellent reproducibility.…”
Section: Discussionmentioning
confidence: 99%
“… 4 , 6 There are some various types of surgical techniques, namely, labral repair alone without cyst decompression, cyst decompression through labral tear with labral repair, and cyst excision through superior capsule window with labral repair. 7 , 8 , 9 …”
mentioning
confidence: 99%